MiR-29b Expression Is Associated With Disease-Free Survival in Patients With Ovarian Serous Carcinoma. Issue 4 (1st April 2009) - Flavin, Richard; Smyth, Paul; Barrett, Ciara; Russell, S.; Wen, Hannah; Wei, Jianjun; Laios, Alex; O'Toole, Sharon; Ring, M.; Denning, K.; Li, J.; Aherne, S.; et al.
Abstract : Micro-RNAs are a group of small noncoding RNAs approximately 22 nucleotides in length. Recent work has shown differential expression of mature micro-RNAs in human cancers. We characterized the alteration in expression of miR-29b in ovarian serous carcinoma. miR-29b expression was analyzed using quantitative stem-loop reverse transcriptase polymerase chain reaction on a set of 50 formalin-fixed, paraffin-embedded ovarian serous carcinoma samples. Protein expression of p53, estrogen receptor, progesterone receptor, human epidermal growth factor receptor 2, Ki-67, and insulinlike growth factor 1 was quantified in the corresponding tissue microarray. The expression profile of miR-29b was correlated with clinicopathological and patient survival data. We provide definitive evidence that miR-29b is down-regulated in a significant proportion of ovarian serous carcinomas and is associated with specific clinicopathological features, most notably high miR-29b expression being associated with reduced disease-free survival.